KAJIAN PAKAN BERSUMBER ENERGI TINGGI PADA PEMBENTUKKAN MONYET OBES - Oktarina, Ria; Mansjoer, Sri Supraptini; Astuti, Dewi Apri; Suparto, Irma Herawati; Sajuthi, Dondin (Perhimpunan Biologi Indonesia, 2010)
ABSTRACTHigh Energy Diet to Develop Obese Animal Model in Cynomolgus Monkeys (Macacafascicularis). Obesity is a primary predisposition for diseases such as metabolic syndrome(insulin resistance, blood lipid abnormality, and hypertension), type 2 diabetes, andcardiovascular disease. The effort to overcome obesity is needed by understanding thedevelopment of obesity. Therefore, it is urgent to carry out preclinical trials by using an obeseanimal model however it is still limited. The objective of this research was to study the effect ofhigh energy diet with animal fat and soluble carbohydrate to produce obese cynomolgusmonkeys (Macaca fascicularis). Animals used in this study were 15 adult males dividedequally into three treatment groups and were given diets for 4 months. The 3 groups were 1)receiving diet A consists of beef tallow without egg yolk; 2) receiving diet B consists of beeftallow and egg yolk, (energy 4,207 cal/g, fat 19.62%, and starch 60.34% in both first two diet) 3)receiving diet C consists of monkey chow as control (energy 4,330 cal/g, fat 5.55%, and starch51.38%). Measurement were taken every four weeks for body weight, crown rump length, hipdiameter, abdominal skin thickness, body mass index (BMI), nutrient consumption anddigestibility. Results showed that animals received diet B had significant increase in bodyweight and BMI at week 4 and 8. Hip diameter and abdominal skin thickness were significantstarting at week 4 in animals receiving diet with egg yolk (p<0.05) compared to the other twogroups. Protein consumption and digestibility in group with diet A and B was lower (p<0.05)compared to control animals. However, digestibility for dry matter, fat, starch and energy wereabout 90%, meaning that the rations were considered adequate in developing obese monkey.The diet formula containing tallow and egg yolk increased body weight based on BMI criteriaabove 25 kg/m2.Key words: obesity, cynomolgus, egg yolk, body mass index, digestibility